Pharmacological Inhibition of Gal-3 in Mesenchymal Stem Cells Enhances Their Capacity to Promote Alternative Activation of Macrophages in Dextran Sulphate Sodium-Induced Colitis - Bojana Simovic Markovic; Aleksandar Nikolic; Marina Gazdic; Jasmin Nurkovic; Irena Djordjevic; Nebojsa Arsenijevic; Miodrag Stojkovic; Miodrag L. Lukic; Vladislav Volarevic (Hindawi Limited, 2016)
Transplantation of mesenchymal stem cells (MSCs) reduces the severity of dextran sulphate sodium- (DSS-) induced colitis. MSCs are able to secrete Galectin-3 (Gal-3), a protein known to affect proliferation, adhesion, and migration of immune cells. We investigate whether newly synthetized inhibitor of Gal-3 (Davanat) will affect production of Gal-3 in MSCs and enhance their potential to attenuate DSS-induced colitis. Pharmacological inhibition of Gal-3 in MSCs enhances their capacity to promote alternative activation of peritoneal macrophages in vitro and in vivo. Injection of MSCs cultured in the presence of Davanat increased concentration of IL-10 in sera of DSS-treated animals and markedly enhanced presence of alternatively activated and IL-10 producing macrophages in the colons of DSS-treated mice. Pharmacological inhibition of Gal-3 in MSCs significantly attenuates concentration of Gal-3 in sera of DSS-treated animals, indicating that MSCs produce Gal-3 in this disease. In conclusion, our findings indicate that Davanat could be used for improvement of MSC-mediated polarization towards immunosuppressive M2 phenotype of macrophages.